Customs, Traditions and Religious Occasions of the Moroccan Jews - Saeed, Marwa Majid; Abdullah, Samira Abdul Razzaq (Journal of Ecohumanism, 2024)
Customs and beliefs constituted an integral part of the religious doctrine of the Jewish community in Morocco, blending with it to the point of inseparability. This reality has been vividly depicted in historical writings. These traditions were influenced by religious beliefs but were also deeply shaped by the environment in which members of the Jewish community lived in Morocco. This reciprocal interaction left its mark on the social reality. The Jewish community formed a fundamental element of the societal fabric, interacting with Moroccan inhabitants in markets, seasonal events, and through trade that transcended vast geographic regions, under the framework of the "Dhimmi" status. They engaged in various forms of commerce, shared worship practices within a unified context, celebrated their joys with the same chants, endured famine and hardship with equal resilience and shared hope, and prayed for rain during droughts in the same language, gestures, and supplications.